Prevalence of Pulmonary Hypertension in Chronic Kidney Disease Patients at a Tertiary Hospital (Pakistan Journal of Kidney Diseases, 2025)
Background:Pulmonary hypertension (PH) is a recognized cardiovascular complication in patients with chronic kidney disease (CKD), particularly in advanced stages. Its presence is associated with increased morbidity, hospitalizations, and mortality. Despite its clinical significance, data on PH prevalence in CKD patients in low-resource settings remain limited.Objective:To determine the prevalence of PH among patients with CKD presenting to a tertiary care nephrology department and to assess its association with demographic and clinical characteristics.Methods:This descriptive cross-sectional study was conducted at the Department of Nephrology, XXXX, from December 2020 to June 2021. A total of 194 patients aged 20–60 years with CKD stage III to V were included. PH was diagnosed using transthoracic echocardiography based on pulmonary artery systolic pressure >35 mmHg and tricuspid regurgitant velocity >3.4 m/s. Patient demographics, comorbidities (diabetes, hypertension), and disease duration were recorded. Statistical analysis was performed using SPSS version 22, with p ≤ 0.05 considered significant.Results:Among 194 patients, 118 (60.8%) were male and the mean age was 49.2 ± 7.14 years. PH was identified in 91 patients (46.9%). Significant associations were observed between PH and male gender (p=0.001), DM (p=0.002), smoking history (p=0.026), disease duration >1 year (p=0.015), and advanced CKD stage (p=0.001). No statistically significant relationship was found with hypertension or obesity.Conclusion:PH is highly prevalent in patients with CKD and correlates with several modifiable and disease-related factors. Routine screening for PH in high-risk CKD patients is recommended for early diagnosis and timely management to reduce cardiovascular complications and improve patient outcomes.
Keywords: pulmonary hypertension; chronic kidney disease; hypertension; diabetes mellitus; coronary artery disease